KEMAMPUAN BERINOVASI DOSEN PGSD FIP UNIVERSITAS NEGERI JAKARTA - Iva Sarifah (Perspektif Ilmu Pendidikan, 2008)
Assuming that the leacture’s ability to make innovation in the instructional activities can improve both the quality of instructional process and the quality of the student’s learning achievement, this research was conducted to describe the the innovative activities performed by the lecturers in Primary School Teacher Education (PGSD) of School of Education, State University of Jakarta. The research conducted in the odd semester of the academic year 2007/2008, randomly selected 30 lectures of the Department as the respondents. From the data collected using questionair and analysed descriptively, the research concludes based on their teachng experience, the lectures with more than 15 years’ teaching experience are more innovative than those with less experience.